Role of Multislice CT Imaging in Predicting the Visibility of the Round Window during Cochlear Implantation - Kailash Kumar Daseja, Sushma Qadir, Bhagwan Das, Imran Khan Memon, Pirya Nangdev, Shaiq Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To envisage the visibility of round window nichein pediatric cochlear implantation by using computed tomography. Study design: Retrospective study Place and duration of study: Department of Radiology, Chandka Medical College Hospital, Larkana from 1st July 2021 to 31st March 2022. Methodology: Fifty five patients underwent the procedure of unilateral-cochlear implantation. Slices of round window niche and round window membrane were selected for visualization through HRCT imaging. The temporal bone imaging through high resolution computed tomography scans; before and after the operation were examined in detailed and scored. Each round window membrane and round window niche was then visualized for its visibility. The sensitivity as well as specificity of high resolution computed tomography imaging in prediction of round window membrane visuality were calculated. Results: The comparison of predictive values showed that the positive-predictive value of RWM was 73.1% and negative as 91.2%. The sensitivity as well as the specificity of HRCT identification in prediction difficulty in visualizing RWM was 79% and 87% respectively. Conclusion: Pre-operative high resolution computed tomography was proved helpful in visualization of detecting round window niche. Key words: CT scan; Cochlear implantation; Round window niche; Pediatrician